LRS Bianchi type-I Universe with anisotropic dark energy and special form of deceleration parameter in f (R, T) gravity - Wankhade, Rajesh; Bansod, A.S. (International Journal of Advanced Astronomy, 2018)
In this paper, LRS Bianchi type-I space-time is considered in the presence of perfect fluid source in the frame work of gravity (Harko et al. in Phys.Rev. D 84:024020, 2011) where is an arbitrary function of Ricci scalar and trace of the energy momentum tensor . The Einstein’s field equations have been solved by taking into account the special form of deceleration parameter (Singha A., Debnath U.: Int.J. Theor. Phys.48, 2009). We observe that in f (R, T) gravity, an extra acceleration is always present due to coupling between matter and geometry. The geometrical and physical aspect of the model is also studied.